1997
DOI: 10.1152/ajpendo.1997.273.2.e233
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic responses from rest to steady state determine contractile function in ischemic skeletal muscle

Abstract: Skeletal muscle contraction during ischemia, such as that experienced by peripheral vascular disease patients, is characterized by rapid fatigue. Using a canine gracilis model, we tested the hypothesis that a critical factor determining force production during ischemia is the metabolic response during the transition from rest to steady state. Dichloroacetate (DCA) administration before gracilis muscle contraction increased pyruvate dehydrogenase complex activation and resulted in acetylation of 80% of the free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
120
8

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(142 citation statements)
references
References 24 publications
14
120
8
Order By: Relevance
“…At the onset of exercise there is a delay in the activation of PDC and formation of acetyl-CoA which appears to be associated with an increase in the contribution of substrate level phosphorylation to energy metabolism (Timmons et al 1997;Howlett et al 1999). When this delay in PDC activation was circumvented by maximally activating PDC using dichloroacetate (DCA) prior to contraction (Timmons et al 1997(Timmons et al , 1998Howlett et al 1999), a reduction in muscle PCr hydrolysis and lactate formation was observed within the first few minutes of exercise. This finding is in contrast with the 584 Figure 2 Muscle PDC activity and acetylcarnitine concentrations at rest and after 10 min of exercise in the CON and CHO trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the onset of exercise there is a delay in the activation of PDC and formation of acetyl-CoA which appears to be associated with an increase in the contribution of substrate level phosphorylation to energy metabolism (Timmons et al 1997;Howlett et al 1999). When this delay in PDC activation was circumvented by maximally activating PDC using dichloroacetate (DCA) prior to contraction (Timmons et al 1997(Timmons et al , 1998Howlett et al 1999), a reduction in muscle PCr hydrolysis and lactate formation was observed within the first few minutes of exercise. This finding is in contrast with the 584 Figure 2 Muscle PDC activity and acetylcarnitine concentrations at rest and after 10 min of exercise in the CON and CHO trials.…”
Section: Discussionmentioning
confidence: 99%
“…Classically, the extent of this anaerobic ATP production through substrate level phosphorylation at the onset of exercise has been attributed to a lag in blood flow and oxygen delivery to the contracting muscle (Margaria et al 1963). More recently, however, it has been demonstrated that the activity of PDC and the availability of acetyl groups to the tricarboxylic acid (TCA) cycle are important determinants of the metabolic responses during the onset of exercise (Timmons et al 1997(Timmons et al , 1998. The PDC controls the rate-limiting step in CHO oxidation, the oxidative decarboxylation of pyruvate to acetyl-CoA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Following 60 min of pretreatment with GPi or vehicle, electrically evoked submaximal isometric muscle contractions were induced (1 Hz, 0.3 ms, 2 V) for 60 min according to methods previously described (20,45), and tension development was recorded. At the start of contraction, muscle blood flow was increased twofold from the resting rate (15 ml ⅐ min Ϫ1 ⅐ 100 g muscle tissue Ϫ1 ) to improve oxygen and substrate delivery.…”
Section: Methodsmentioning
confidence: 99%
“…Whether these improvements in endurance performance are due to glycogen sparing as a result of a carnitine mediated increase in fat oxidation, or the reported effect of carnitine on glucose disposal requires further investigation, but due to the nature of the time trial this seems unlikely. In fact, it is the reduced reliance on non-oxidative ATP production from carbohydrate oxidation (increase acetyl group buffering and reduced lactate accumulation) that is the more likely cause of the increased endurance performance observed [33]. Moreover, with the acetyl-group buffering role of carnitine in mind, increasing muscle carnitine content may also allow a greater stockpiling of acetylcarnitine during a prior 'warm-up' exercise, which would then serve as a useful immediate supply of acetyl groups at the onset of a subsequent high-intensity performance task and again reduce the reliance on non-oxidative ATP production [34].…”
Section: Effect Of Increasing Muscle Carnitine Content On Endurance Pmentioning
confidence: 99%